"Metabolism of Odontoblast-like cells submitted to transdentinal irradiation with blue and red LED". (November 2017) - Almeida, Leopoldina de Fátima Dantas de; Basso, Fernanda Gonçalves; Turrioni, Ana Paula Silveira; de-Souza-Costa, Carlos Alberto; Hebling, Josimeri
Highlights: The odontoblast like cells MDPC-23 exposed to red LED (630 nm) and blue LED (540) were evaluated with regards to celular metabolismo. We evaluated two different power densities (40 e 80 mW/cm 2 ) according to waveleght. Red LED at the energy dose of 4 J/cm 2 increased cell viability. Blue LED was not capable of photobiostimulating cell proliferation. Abstract: Objectives: The present study evaluated the trans-dentinal effect of light emitting diodes (LEDs) irradiation on the metabolism of odontoblast-like cells. Methods: Seventy-two dentin discs (0.2 mm thick) were obtained from human molar teeth. MDPC-23 cells (20, 000 cells/disc) were seeded on the pulpal side of the discs using DMEM, supplemented with 10% fetal bovine serum (FBS). After 12 h, the culture medium was replaced with DMEM containing 0.5% FBS. After additional 12 h, blue (455 ± 10 nm) or red (630 ± 10 nm) LEDs were used at irradiances of 80 and 40 mW/cm 2, respectively, to irradiate the occlusal side of the discs. The energy doses were fixed at 2 or 4 J/cm 2 . Cell viability, alkaline phosphatase activity (ALP), total protein production and collagen synthesis were evaluated 72 h after irradiation. Data were submitted to Kruskal-Wallis and Mann-Whitney tests (α=0.05). Results: Red light promoted proliferative effects at the energy dose of 4 J/cm 2 . Conversely, cell cultures irradiated with 2 J/cm 2 emitted by the blue light showed reduced viability. ALP production was stimulated by red light in comparison with blue light at 4 J/cm 2 . Total protein production was reduced after exposure to blue light at 4 J/cm 2, while no effect was observed on collagen production. Conclusions: Irradiation with red LED at 4 J/cm 2 bio-stimulated the viability of odontoblast-like cells, whilst blue light had unfavorable effects on the cellular metabolism.